(untitled) (Journal of the College of Basic Education, 2020)
Allah has glorified attributes and names derived from the names of Hosn and Kaliml, such as Al-Alem and Al-Alam, called and worship with it, and the Surat Ana’am has a great aspect related to it. And the importance of science in this great adjective in the life of the believer and increase his faith in Allah, and to help the human to live in comfortable style. my Research has been divided into two subjects, begins with an introduction , topic, and conclusion, while the first subject was about " the knowledge of Allah about Cosmic phenomena" while the second subject was about " the knowledge of Allah about humans, and then came the conclusion in which the results.